Analysis and Design of Web-Based E-Commerce At CMYK.Project - Ramadhan Sonida (Bina Nusantara University, 2021)
The research objective is to design an e-commerce website in the CMYK.PROJECT company where customers can make purchases in the company's website and the company can also provide information and serve the customers in e-commerce website. Research methods in this study, using data collection and methods of system design e-commerce. Collecting data in this thesis is done through interviews, questionnaires, and direct observation to the company. In this thesis analyzes used is the analysis of SEM-PLS and E-Commerce Strategy. Designing for the e-commerce company in this thesis using OOAD and Framework 7C. Results is in getting the results of e-commerce website for the company to sell products to customers, and customers can make purchases in the e-commerce company. The conclusion obtained is with their e-commerce website, it can shorten the sales process of the company's products to customers, and also facilitates the transaction purchase the company's products.